Comparative Genomics of the Herbivore Gut Symbiont Lactobacillus reuteri Reveals Genetic Diversity and Lifestyle Adaptation - Yu, Jie; Zhao, Jie; Song, Yuqin; Zhang, Jiachao; Yu, Zhongjie; Zhang, Heping; Sun, Zhihong (Frontiers in Microbiology, 2018)
Lactobacillus reuteri is a catalase-negative, Gram-positive, non-motile, obligately heterofermentative bacterial species that has been used as a model to describe the ecology and evolution of vertebrate gut symbionts. However, the genetic features and evolutionary strategies of L. reuteri from the gastrointestinal tract of herbivores remain unknown. Therefore, 16 L. reuteri strains isolated from goat, sheep, cow, and horse in Inner Mongolia, China were sequenced in this study. A comparative genomic approach was used to assess genetic diversity and gain insight into the distinguishing features related to the different hosts based on 21 published genomic sequences. Genome size, G + C content, and average nucleotide identity values of the L. reuteri strains from different hosts indicated that the strains have broad genetic diversity. The pan-genome of 37 L. reuteri strains contained 8,680 gene families, and the core genome contained 726 gene families. A total of 92,270 nucleotide mutation sites were discovered among 37 L. reuteri strains, and all core genes displayed a Ka/Ks ratio much lower than 1, suggesting strong purifying selective pressure (negative selection). A highly robust maximum likelihood tree based on the core genes shown in the herbivore isolates were divided into three clades; Clades A and B contained most of the herbivore isolates and were more closely related to human isolates and vastly distinct from Clade C. Some functional genes may be attributable to host-specific of the herbivore, omnivore and sourdough groups. Moreover, the numbers of genes encoding cell surface proteins and active carbohydrate enzymes were host-specific. This study provides new insight into the adaptation of L. reuteri to the intestinal habitat of herbivores, suggesting that the genomic diversity of L. reuteri from different ecological origins is closely associated with their living environment.